Chapter 5.3 The Profession of Research Management and Administration in Nigeria - Abiodun Akindele; Makinde Opeyemi (Emerald Publishing Limited, 2023)
This chapter explains the evolution of Research Management and Administration (RMA) in Nigeria with its achievements and challenges arising from the participation of relevant stakeholders and current practitioners from 24 universities in Nigeria. The layout covers the prerequisites for RMA, its development, and its implementations. Nonetheless, the research shows that the non-professionalisation of RMA in Nigeria is not only a barrier but also a challenge to the emergence of a profession which can be resolved by the implementation of approved/not-approved career structures for RMA in Nigeria. Findings from a survey show that a tripartite group is involved in the present-day RMA. Moreover, submissions by participants show that in the next two decades, RMA is expected to attract both academic and administrative staff with leadership by academic staff. The research supported the hypothesis that academic staff is most suitable to pilot RMA, nonetheless, when core research assignments for academic staff increase shortly, RMA will most likely be directed by administrative staff.
10.1108/978-1-80382-701-820231036; 10.1108/978-1-80382-701-820231036; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262